2008
DOI: 10.1128/jb.00006-08
|View full text |Cite
|
Sign up to set email alerts
|

Role of Staphylococcus aureus Catalase in Niche Competition against Streptococcus pneumoniae

Abstract: Nasal colonization by Staphylococcus aureus is a major predisposing factor for subsequent infection. Recent reports of increased S. aureus colonization among children receiving pneumococcal vaccine implicate Streptococcus pneumoniae as an important competitor for the same niche. Since S. pneumoniae uses H 2 O 2 to kill competing bacteria, we hypothesized that oxidant defense could play a significant role in promoting S. aureus colonization of the nasal mucosa. Using targeted mutagenesis, we showed that S. aure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
64
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 21 publications
5
64
0
1
Order By: Relevance
“…The core metabolic network also contained known metabolic virulence determinants including catalase, an enzyme that hydrolyzes hydrogen peroxide into water and oxygen and that is used in the clinical laboratory to distinguish staphylococci from enterococci and streptococci. Catalase production and oxidant resistance have been shown to be predisposing factors for nasal colonization and subsequent infection (32).…”
Section: Known S Aureus Virulence Factors Are Unequally Distributed mentioning
confidence: 99%
“…The core metabolic network also contained known metabolic virulence determinants including catalase, an enzyme that hydrolyzes hydrogen peroxide into water and oxygen and that is used in the clinical laboratory to distinguish staphylococci from enterococci and streptococci. Catalase production and oxidant resistance have been shown to be predisposing factors for nasal colonization and subsequent infection (32).…”
Section: Known S Aureus Virulence Factors Are Unequally Distributed mentioning
confidence: 99%
“…In line with the theory of H 2 0 2 interference, Park et al demonstrated that S. aureus catalase expression contributes to its ability to colonize and survive in the presence of S. pneumoniae in an in vivo mouse model of nasal co-colonization. 20 However, in a neonatal rat model, Margolis observed that S. aureus density did not differ whether co-colonized with hydrogen peroxide producing or non-producing S. pneumoniae, or whether catalase or non-catalase producing S. aureus strains were tested. 21 To assess the role of hydrogen peroxide in the patterns of human co-colonization, Regev-Yochay et al assessed the variation of bactericidal activity in S. pneumoniae strains isolated from children co-colonized with S. pneumoniae and S. aureus compared to those colonized only with S. pneumoniae.…”
mentioning
confidence: 99%
“…39 Esto puede deberse a que los materiales analizados en este estudio no estuvieron en contacto con S. aureus y C. albicans o que otros tipos de microorganismos pudieron causar su inhibición. 43,44 Otra razón es la metodología utilizada, ya que el grupo de Ensinas colocó los nú-cleos en medio de enriquecimiento antes de sembrarlos en medios comunes, aumentando así la concentración de células de estos microorganismos.…”
Section: Discussionunclassified
“…39 This may be due to the fact that the materials analyzed in this study were not in contact with S. aureus and C. albicans, or other types of microorganisms could cause their inhibition. 43,44 Another reason has to do with the used methodology, since Ensinas et al placed the cores in an enrichment medium before immersing them in common media, thus increasing the concentration of cells of these microorganisms.…”
Section: Discussionmentioning
confidence: 99%